Assessment of Ultimate Bearing Capacity of Static Loading Pile Based on Cusp Catastrophe Theory - Jibao Yang; Xing Huang; Hao Ni; Shilong Hao; Fudong Liu; Zhangrong Liu (Advances in Civil Engineering)
Determining the ultimate bearing capacity of pile is important for reasonable design of the pile. In this paper, a cusp catastrophe theory-based method was proposed for assessing the ultimate bearing capacity of static loading pile. Firstly, a three-parameter quartic polynomial in accordance with the standard form of cusp catastrophe model is proposed and used to fit the experimentally obtained Q–S curve. The parameters which allow the polynomial to produce best fitting to the Q–S curve are taken to identify the stability of the pile following a simple procedure. Then, the proposed method was verified against 10 Q–S curves obtained from field tests at Jinqiao-Meiya and Jinqiao-Chunyu areas of Shanghai. Results show that the ultimate bearing capacities of the piles identified by the proposed method were comparable to those identified by the JGJ 106-2014 standard method. Finally, it is found that the stability of the pile identified by the proposed method and the mechanical state of the pile identified by the Golden Section approach were correlated closely.